Foliar applications of bio-fabricated selenium nanoparticles to improve the growth of wheat plants under drought stress - Ikram, Muhammad; Raja, Naveed Iqbal; Javed, Bilal; Mashwani, Zia-ur-Rehman; Hussain, Mubashir; Hussain, Mujahid; Ehsan, Maria; Rafique, Noman; Malik, Khafsa; Sultana, Tahira; Akram, Abida (Green processing and synthesis, 2020)
The present study was aimed to biosynthesize selenium nanoparticles (SeNPs) and assess their foliar applications to improve the growth of wheat plants under controlled irrigation and drought stress. Bud aqueous extract of L. was used as a reducing and stabilizing agent of SeNPs followed by their optical and morphological characterization by using ultraviolet-visible spectroscopy, scanning electron microscopy, Fourier-transform infrared, and energy dispersive X-ray analysis. Various concentrations of SeNPs (10, 20, 30, and 40 mg/L) were applied exogenously to drought-tolerant (V1) and drought-susceptible (V2) wheat varieties at the trifoliate stage. Under the positive control conditions, plants were irrigated with 450 mL of water/pot (100% field capacity); and under water-deficit environment, plants were irrigated with 160 mL of water/pot (35% field capacity). Remarkable increase in plant height, shoot length, shoot fresh weight, shoot dry weight, root length, root fresh weight, root dry weight, leaf area, leaf number, and leaf length has been observed when 30 mg/L concentration of SeNPs was used. However, the plant morphological parameters decreased gradually at higher concentrations (40 mg/L) in both selected wheat varieties. Therefore, 30 mg/L concentration of SeNPs was found most preferable to enhance the growth of selected wheat varieties under normal and water-deficient conditions.